KAJIAN TEORITIS PENDEKATAN HUMANISTIK (AL-MADKHAL AL-INSAN) DALAM PEMBELAJARAN BAHASA ARAB - Titin Fatimah; Didin Faqihuddin; Fajri Ardiansyah (Albariq: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to find out how the models and methods of implementing Arabic language learning use a humanistic approach. The research method used is using qualitative methods, data collection techniques in research are documentation techniques. And the data analysis technique is content analysis. Based on the results of the author's study of the humanistic approach in learning Arabic, it was found that the humanistic approach is very important in the development of student learning. The humanistic approach pays attention to human qualities that have free will and the potential to develop themselves. This research study proves that the concept of a humanistic approach in learning will lead to an attitude of respect for human development without departing from religious values. The humanistic approach in learning Arabic provides opportunities for students to train their thinking power to be more creative and develop.